2013
DOI: 10.2214/ajr.12.10395
|View full text |Cite
|
Sign up to set email alerts
|

Can Dual-Time-Point 18F-FDG PET/CT Differentiate Malignant Salivary Gland Tumors From Benign Tumors?

Abstract: Dual-time-point FDG PET/CT is not useful for discriminating between benign and malignant salivary gland tumors, because benign tumors also show high FDG uptake, which increases in the delayed phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 12 publications
0
11
0
2
Order By: Relevance
“…Toriihara et al [18] found that dual-time-point FDG PET/CT was not useful for discriminating benign versus malignant salivary gland tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Toriihara et al [18] found that dual-time-point FDG PET/CT was not useful for discriminating benign versus malignant salivary gland tumors.…”
Section: Discussionmentioning
confidence: 99%
“…An association of these findings with the sertoli cell tumor was considered very unlikely. Furthermore a human study concluded that a differentiation between benign and malignant salivary gland tumors is not possible by FDG PET/CT based on an increased FDG uptake [32]. Therefore, these findings were not included in further treatment decisions for the dog.…”
Section: Discussionmentioning
confidence: 99%
“…In a third study on 26 esophageal cancer patients specificity to detect metastatic lesions was improved when retention index (RI) 10% was used to supplement the early SUVmax of ≥ 2.5 (32) . On the other hand there are other studies that reported no improvement in diagnostic accuracy by the use of delayed imaging (33)(34)(35)(36) . In most of these studies the delayed SUVmax or RI were used separately versus the early SUVmax and not in conjunction with the early SUVmax.…”
Section: Discussionmentioning
confidence: 94%